Skeletal muscle expresses the extracellular cyclic AMP–adenosine pathway - Chiavegatti, T (Nature Publishing Group, 2007)
BACKGROUND AND PURPOSE: cAMP is a key intracellular signalling molecule that regulates multiple processes of the vertebrate skeletal muscle. We have shown that cAMP can be actively pumped out from the skeletal muscle cell. Since in other tissues, cAMP efflux had been associated with extracellular generation of adenosine, in the present study we have assessed the fate of interstitial cAMP and the existence of an extracellular cAMP-adenosine signalling pathway in skeletal muscle. EXPERIMENTAL APPROACH: cAMP efflux and/or its extracellular degradation were analysed by incubating rat cultured skeletal muscle with exogenous cAMP, forskolin or isoprenaline. cAMP and its metabolites were quantified by radioassay or HPLC, respectively. KEY RESULTS: Incubation of cells with exogenous cAMP was followed by interstitial accumulation of 5′-AMP and adenosine, a phenomenon inhibited by selective inhibitors of ecto-phosphodiesterase (DPSPX) and ecto-nucleotidase (AMPCP). Activation of adenylyl cyclase (AC) in cultured cells with forskolin or isoprenaline increased cAMP efflux and extracellular generation of 5′-AMP and adenosine. Extracellular cAMP-adenosine pathway was also observed after direct and receptor-dependent stimulation of AC in rat extensor muscle ex vivo. These events were attenuated by probenecid, an inhibitor of ATP binding cassette family transporters. CONCLUSIONS AND IMPLICATIONS: Our results show the existence of an extracellular biochemical cascade that converts cAMP into adenosine. The functional relevance of this extracellular signalling system may involve a feedback modulation of cellular response initiated by several G protein-coupled receptor ligands, amplifying cAMP influence to a paracrine mode, through its metabolite, adenosine.